Giving and taking in dictator games – differences by gender? A replication study of Chowdhury et al. (Southern Economic Journal, 2017) - Korbinian von Blanckenburg; Eva Tebbe; Anja Iseke (Journal of Comments and Replications in Economics (JCRE), 2023)
In a recent simulation study, Goodman et al. (2019) compare several methods with regard to their type I and type II error rates when considering a thick null hypothesis that includes all values that are practically equivalent to the point null hypothesis. They propose a hybrid decision criterion only declaring a result "significant" if both a small p-value and a sufficiently large effect size are obtained. We successfully verify the results using our own software code in R and discuss an additional decision method that is tailored to maintain a pre-defined false positive rate. We confirm that the hybrid decision criterion has comparably low error rates in checkable settings but point out that the false discovery rate cannot be easily controlled by the researcher. Our analyses are readily accessible and customizable on github.com/drehero/goodman-replication.
https://doi.org/10.15456/j1.2021138.1037237398
Keywords: C91; D64; D84; J16; 330; Replication Study